The Concept Of Legal Reasoning Of Judges In Islamic Law Regarding Legal Decisions For Drug Addicts In The Mandailing Natal District Court - Yusuf Harahap, Bahtiar; Sukiati, Sukiati; Tanjung, Dhiauddin (Journal of Law, Politic and Humanities, 2024)
This research examines the concept of legal reasoning of judges in Islamic law related to legal decisions for drug addicts in the Mandailing Natal District Court. Legal reasoning in Islamic law involves interpreting the Quran, Hadith, Ijma, and Qiyas to reach a just decision. This research uses a qualitative approach with a case study method, analysis of decision documents, interviews with judges, and trial observation. The results showed that the judge combined the principles of Islamic law with Indonesian positive law. In the case of drug addicts, judges consider: Justice and Public Welfare: A verdict that not only punishes but also provides opportunities for rehabilitation. Interpretation of Islamic Law Sources: Referring to the Quran, Hadith, and scholarly opinions on punishment for drug addicts. Social Context and Positive Law: Ensuring the verdict is in line with national laws and local conditions. Rehabilitation and Protection of Human Rights: Support for the rehabilitation and recovery of addicts. In conclusion, the concept of judges' legal reasoning in Islamic law plays an important role in determining decisions that are fair, humane, and support the recovery and welfare of society. Practical implications include improving judges' understanding of Islamic legal reasoning and the integration of rehabilitative approaches in court decisions.